Myotonometric Assessment of Achilles Tendon and Gastrocnemius Stiffness in Recreationally Active Young Adults: Reliability, Impact of Sex, and Links to Linear Sprint - Matic Sašek; Petra Brnelić; Žiga Kozinc (Montenegrin Journal of Sports Science and Medicine, 2026)
This study examined the relationship between passive Achilles tendon (AT) and gastrocnemius (GAS) stiffness, measured by myotonometry, and 40-m sprint performance across acceleration and maximal velocity phases, while accounting for sex differences. Twenty-one student athletes (10 males, 11 females) underwent bilateral passive stiffness assessments of the AT and GAS using MyotonPRO, followed by 40-m sprint testing with 10, 20, 30, and 40 m splits. Reliability was assessed using the intraclass correlation coefficient (ICC) and coefficient of variation (CV). Sex differences were examined with independent t-tests. Partial correlations controlling for sex were used to assess associations between passive stiffness and sprint performance. Passive stiffness and sprint variables demonstrated excellent within-session reliability (ICC = 0.95–0.99; CV < 5%). Males showed significantly greater passive GAS stiffness bilaterally (p = 0.006–0.049) and faster sprint times at 30 m (p = 0.040) and 40 m (p < 0.001), while passive AT stiffness did not differ significantly between sexes. Partial correlations indicated that greater passive AT stiffness in both legs was associated with faster sprint times at 10 m (r = -0.46 and -0.58, p = 0.008 and 0.043) and 20 m (r = -0.49 and -0.58, p = 0.008 and 0.029). No associations were observed at 30 m or 40 m, nor between passive GAS stiffness and sprint performance. Myotonometry provides reliable measures of AT and GAS stiffness. Greater passive AT stiffness is associated with faster acceleration sprint performance independent of sex.